Managing our Wetlands: some result of the function of a Wetland in Perak, Malaysia - Wan Ruslan Ismail,; Ahyauddin Ali, (Environmental Management Society, Malaysia, 2002)
The global extent of wetlands is estimated to be from 7 to 8 million km2 and, compared to other ecosystems; wetlands are an extremely productive part of the landscape with average annual production above 1000gC m-2 yr-1. In Malaysia and other developing countries, the wetlands are becoming a threatened landscape especially due to development. Based on this scenario of the depleting wetland of the world, a study was carried out to investigate the form and function of natural wetland in regulating floodwaters and nutrients input and output. A Beriah swamp in north Perak was chosen as a wetland ecosystem for this study. Input of water and nutrients to the wetland and the output from the wetland were investigated. Result indicated that generally a swamp does act as nutrient in the system. The dissolved loads were being added in the swamp or wetland system and flushed out of the swamp ecosystem. Individual evaluation of the nutrient shows that the nitrogen component (nitrate and ammonia) was retained in the wetland system, whereas phosphate and TSS were ‘generated’ and flushed out of the system. The way in which nitrate and ammonia was transported shows that Beriah Swamp does act as nutrient trap, as has been observed elsewhere. The dampening effect of the oscillation on discharge and solute loads was also observed to take place in this short-term study. This paper end with discussions on the challenges faced by many wetlands of the world in the 21st century